Semi-bridging σ-silyls as Z-type ligands. Issue 24 (27th February 2020) - Frogley, Benjamin J.; Hill, Anthony F.; Sharma, Manab; Sinha, Arup; Ward, Jas S.
Abstract : The reactions of SiHPh(NCH2 PPh2 )2 C6 H4 -1, 2 with zerovalent group 10 reagents afford the homoleptic bimetallic complexes [M2 μ-κ 3 -Si, P, P ′-SiPh(CH2 PPh2 )2 C6 H4 2 ] (M = Ni, Pd, Pt) in which the M–M bond is unsymmetrically bridged by two σ-silyl groups. Abstract : The reactions of SiHPh(NCH2 PPh2 )2 C6 H4 -1, 2 with a range of zerovalent group 10 reagents afford the homoleptic bimetallic complexes [M2 μ-κ 3 -Si, P, P ′-SiPh(CH2 PPh2 )2 C6 H4 2 ] (M = Ni, Pd, Pt) in which the M–M bond is unsymmetrically bridged by two σ-silyl groups. The asymmetry of the M2 Si2 core increases from Ni through Pd to Pt and is consistent with a bonding description in which one metal acts as an electron pair donor to a trigonal bipyramidal 'Z-type' silicon centre, reminsicent of semi-bridging coordination by CO, carbynes and boryl ligands.